Phymaturus payuniae. Blood parasite - D'amico, Veronica Laura (2016)
We report the intracellular blood parasite Schellackia (Apicomplexa) found in erythrocytes of an individual endemic lizard, Phymaturus payuniae, from La Payunia State Reserve (Mendoza, Argentina). Blood smears were examined under a microscope detecting the parasite in 26/2000 cells. This is the first report of the presence of an intracellular parasite in the genus Phymaturus. Schellackia haemococcidios have been reported for lizards in America, Europe and Asia and this, to our knowledge, is the first record for this parasite in northern Patagonia, Argentina.